Ergodic type solutions of differential equations with piecewise constant arguments - Ana Isabel Alonso; Jialin Hong (International Journal of Mathematics and Mathematical Sciences)
We summarize the conditions discovered for the existence of new ergodic type solutions (asymptotically almost periodic, pseudo almost periodic, ...) of differential equations with piecewise constant arguments. Their existence is characterized by introducing a new tool, the ergodic sequences.